Alleviation of restriction by DNA condensation and non-specific DNA binding ligands - Keatch, Steven A. (Oxford University Press, 2004)
During conditions of cell stress, the type I restriction and modification enzymes of bacteria show reduced, but not zero, levels of restriction of unmethylated foreign DNA. In such conditions, chemically identical unmethylated recognition sequences also occur on the chromosome of the host but restriction alleviation prevents the enzymes from destroying the host DNA. How is this distinction between chemically identical DNA molecules achieved? For some, but not all, type I restriction enzymes, alleviation is partially due to proteolytic degradation of a subunit of the enzyme. We identify that the additional alleviation factor is attributable to the structural difference between foreign DNA entering the cell as a random coil and host DNA, which exists in a condensed nucleoid structure coated with many non-specific ligands. The type I restriction enzyme is able to destroy the ‘naked’ DNA using a complex reaction linked to DNA translocation, but this essential translocation process is inhibited by DNA condensation and the presence of non-specific ligands bound along the DNA.